LBRY, Inc.: Scaling and Monetizing a Blockchain Startup. (July 2019) - Mancha, Ruben; Gordon, Steven; Stoddard, Donna
Jeremy Kauffman is a serial entrepreneur with a strong belief in the value of decentralized technology and a firmly held ethic in support of freedom of information. He has founded LBRY to implement a peer-to-peer exchange of multimedia content from producer to viewer or user over a blockchain. This platform runs over an open-source protocol that LBRY had developed for this purpose. In this case, we introduce the blockchain-backed LBRY protocol and the content-sharing platform LBRY built upon it and discuss technical and strategic challenges faced by the startup to grow its user base and number of content providers, generate revenue, and remain competitive. Students analyzing the case will gain an understanding of blockchain, protocols, platforms, and the strategic challenges inherent to managing a technology startup.